작기 중 물관리를 실시한 휴경기 논에서의 온실가스 배출 특성 조사: 순 지구온난화지수 산정(net GWP) - 권효숙(Gwon, Hyo Suk); 김건엽(Kim, Gun Yeob); 최은정(Choi, Eun Jung); 이선일(Lee, Sun Il); 이종식(Lee, Jong Sik) (한국기후변화학회지, 2021)
Approximately 51% of the greenhouse gas (GHG) emissions generated by the agricultural sector in Korea are emitted from rice fields. Despite the extended fallow season, the calculation of GHG emissions from rice fields has been limited to rice cropping season. In this study, we sought to provide information on GHG emission considering the carbon budget in the fallow season. To compare the influence of water management during cropping season and how it affects the fallow season, two different treatments were examined, continuously flooded (CF-fallow) and intermittent drainage (ID-fallow). The emission rates of methane (CH4), nitrous oxide (N2O), and carbon dioxide (CO2) were monitored using the closed chamber method. Changes in soil carbon were estimated using the net ecosystem carbon budget (NECB) method and the net global warming potential (GWP) calculated. Seasonal CH4 and N2O emissions were not significantly different between treatments, but the seasonal CO2 emission for CF-fallow was significantly higher than that of ID-fallow. The net GWP was 5062 kg CO2-eq. ha-1 for CF-fallow and 4433 kg CO2-eq. ha-1 for ID-fallow. Approximately 77% of the calculated net GWP value was affected by the NECB value, followed by 22 ~ 23% affected by N2O emission. In contrast, the influence of methane on net GWP was less than 1%, suggesting little effect on GHG emissions. In order to reduce GHG emissions during the fallow season in rice paddies, carbon enhancement through the input of carbon sources into the soil should be employed. However, since there are concerns about increased CH4 emission from decomposing organic material during the cropping season, additional research on appropriate organic material sources and application methods should be conducted. KCI Citation Count: 0